Perspektif Filsafat Terhadap Etika Manusia dalam Pengelolaan Sumber Daya Alam dan Lingkungan untuk Kehidupan Berkelanjutan - Aldian Syafputra Pratama; Muhammad Sarjan (Lembaga Bale Literasi, 2024)
Currently, development can be seen everywhere, there is a lot of land clearing by infrastructure development which can cause damage to the environment itself which can cause various environmental problems such as floods, landslides, extinction of endangered animals, lack of clean water, increasing air pollution. This research aims to determine the relationship between humans and natural resources and the environment as well as the role of humans in managing natural resources and the environment based on a philosophical perspective. This research is a qualitative descriptive research with data collection using literature study techniques using secondary data. The results and discussion show that the relationship between humans and natural resources and the environment reflects a complex interaction between needs, activities, influences, responsibilities and human awareness of the environment in which they live. So there needs to be a human role in it based on existing ethics and the two environmental ethics have differences, namely the difference in approach between ecopocentric and anthropocentric results in different priorities in managing natural resources and the environment. The ecopocentric approach emphasizes environmental preservation as the main goal, while the anthropocentric approach places more emphasis on the use of natural resources to improve human welfare.